The Johnny Carson show [videorecording (DVD)] - Carson, Johnny, 1925-2005; McMahon, Ed (Timeless Media Group, 2006)
The beginning of over 35 years of joyful entertainment to millions of loyal television fans. Includes four episodes of The Johnny Carson Show, one episode of Who Do You Trust, one episode of The Jack Benny Show, commercial bloopers, and biography.